PENGARUH METODE PEMBERIAN RANSUM PADA SIANG DAN MALAM HARI TERHADAP RESPON FISIOLOGIS AYAM JANTAN TIPE MEDIUM DI KANDANG POSTAL - Evelline Dhea Monica Wijaya; Sri Suharyati; Khaira Nova; Dian Septinova (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2021)
This study aimed to determine the effect of the method of giving rations during the day and night on the physiological response (respiratory rate, rectal temperature, and heart rate) of medium type roosters in postal cages and to determine the effect of the best day and night ration methods on physiological response of medium type rooster in postal cage. This study used a Completely Randomized Design (CRD), consisting of three treatments with six replications, those were P1: 30% day and 70% night ration; P2: 50% day and 50% night ration; P3: 70% day and 30% night ration. The chicken used was male Lohman strain medium type of 144 chickens. The resulting data were analyzed with variance at 5% level. The results showed that the influence of day and night administration method was not different (P > 0.05) on the frequency of breath (51.73 to 55.27 Times/min), rectal temperature (41.13 to 41.16oC), and heart rate frequency (421.2 to 434.7 times/minute). Keywords: Day and night rationing, Medium type rooster, Physiological response, Postal cage